2018
DOI: 10.1371/journal.pone.0203525
|View full text |Cite
|
Sign up to set email alerts
|

The utility of two interview-based physical activity questionnaires in healthy young adults: Comparison with accelerometer data

Abstract: BackgroundAccurate assessment of physical activity is essential to determine the magnitude of the health-related benefits of regular physical activity. While physical activity questionnaires are easy to use, their accuracy in comparison to objective measures has been questioned. The purpose of the present study was to examine the utility of two interview-based questionnaires; a recently-developed instrument, the Simple Physical Activity Questionnaire (SIMPAQ), and the Seven Day-Physical Activity Recall (7DPAR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
1
23
1
Order By: Relevance
“…The duration and intensity of athletic training and recreational physical activities are assessed separately for each day. SIMPAQ was validated with university students by Schilling et al [70] and has shown a moderate to strong correlation to accelerometer data and to established self-report questionnaires (Seven-Day Physical Activity Recall [71] and the short form of the International Physical Activity Questionnaire [72]). Compared to other self-report questionnaires the SIMPAQ is less time consuming [70].…”
Section: Methodsmentioning
confidence: 99%
“…The duration and intensity of athletic training and recreational physical activities are assessed separately for each day. SIMPAQ was validated with university students by Schilling et al [70] and has shown a moderate to strong correlation to accelerometer data and to established self-report questionnaires (Seven-Day Physical Activity Recall [71] and the short form of the International Physical Activity Questionnaire [72]). Compared to other self-report questionnaires the SIMPAQ is less time consuming [70].…”
Section: Methodsmentioning
confidence: 99%
“…In physical activity research, correlation coefficients between self-report and objective measures of physical activity of 0.3 are often reported as acceptable evidence of validity [35][36][37][38][39]. This limited shared variance reflects the challenges associated with both self-report questionnaires and accelerometers when assessing physical activity in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Its validity and reliability have been evaluated in diverse samples over the past 20 years and its psychometric properties are sound (Sarkin et al 1997). It has been correlated with an objective measure of accelerometer (rho = 0.50-0.54, p < 0.001) (Schilling et al 2018). The standardized interview format was as follows: An interviewer explained (e.g.…”
Section: Methodsmentioning
confidence: 99%